Gamification design in computer-supported collaborative learning: towards an approach for tailoring influence principles to player roles - Borges, Simone de Sousa (2017)
Gamification is a term that refers to the use of game design elements in contexts other than video games. In these contexts, the primary goal of gamification is not playful, but rather to motivate users to perform tasks or change behaviors. It is also the goal of gamification, captivate users and influence them to persist in the use of the gamified system. In recent years, we have witnessed a growing interest in gamification and its application in learning environments, especially online. In learning contexts, motivating students to follow up on teaching tasks is an important role for teachers and intelligent educational systems. However, ill-designed gamification interventions can become a distraction capable of interfering on the teaching-learning process. Despite this, most studies in the area remain focused on the potential benefits of gamification and less on investigating systematized solutions to achieve these benefits. Our contribution to the solution of the problem is based on the use of persuasion profiles that take into account the students player roles. We conduct systematic mappings of the literature to gather information about gamification in education, and how group formation in collaborative learning environments. As a result, we created two conceptual frameworks. One framework to help understand and classify group formation in the context of computer-supported collaborative learning, and other to support the definition of player roles in collaborative learning environments. Also, in a preliminary study (N = 481), we adapted and validated for Brazilian Portuguese speakers a scale to measure users susceptibility to persuasion. In another study (N = 149) we developed a theoretical model to map persuasive strategies and different roles of players to support the elaboration of persuasion profiles. Finally, to verify the feasibility of our model, in another study (N = 18) we elaborated prototypes of user interfaces and analyzed the perceived persuasiveness of the interfaces for different players roles and their susceptibility to persuasion. Results show that less motivated students were more likely to accept the suggestions of the prototypes, whereas users with above-average motivation (among observed students) reacted negatively to influence attempts by showing low agreement rates for the requirements of the prototypes. We also observed in the three studies (N = 648) that the number of individuals susceptible to the principle of authority were the lowest, compared to the other influence principles. Few research initiatives have been investigating the development of tailored gamified. One of the reasons for such deficiency is the difficulty of creating computational models based on learners psychological traits (e.g., psychological needs, susceptibility to persuasion, and learner and player roles). However, more worrisome than the ineffectiveness of gamification models based on one-size-fits-all is the risk of designing counterproductive models that could backfire, since the appropriate strategy to motivate an individual may end up discouraging others. Thus, evidence suggest that gamification design could benefit of influence principles, although tailored solutions should be designed to minimize the risks of selecting counter-tailored and ill-defined persuasive strategies.